Analisis Pasar Komoditi Garam Di Indonesia - Aqwa Naser Daulay (Institut Agama Islam Negeri Padngsidimpuan, 2019)
AbstractThe government's desire to achieve salt self-sufficiency still cannot be fulfilled, this is related to the issue of helplessness of people's salt in supplying national salt needs and the phenomenon of the salt import trend is not solely related to supply and demand for salt commodities, but cannot be separated from the trading mechanism which is still considered very bad. Therefore, it is related to the condition of the mechanism of management of the people's salt trade which is still considered to be very poor, and the direction of the chain is not clear. So based on this, the authors are interested in discussing the general description of the mechanism of the people's salt market in Indonesia and the problems faced are based on the preparation of conventional economics and Islam. To find out the answer to the problem the author uses a research methodology with a qualitative approach, because this research method is intended to analyze the phenomena that occur related to the analysis of the theory and the data obtained. The results of the study show that the salt market distortion has occurred due to the existence of monopolistic practices and tallaqi ruqban. The problems that occur in the salt trade system, are caused by weather factors (high rainfall), inadequate land area, technology that still uses traditional systems, domestic salt quality standards, difficulty in finding markets, indications of salt import monopoly practices. AbstrakKeinginan pemerintah untuk swasembada garam belum dapat terpenuhi, hal ini terkait dengan masalah ketidakberdayaan garam dalam memasok kebutuhan nasional dan fenomena tren impor garam tidak semata-mata terkait dengan pasokan dan permintaan komoditas garam, tetapi tidak dapat dipisahkan dari mekanisme perdagangan yang sangat buruk. Karena itu, mekanisme pengelolaan perdagangan garam rakyat dan arah rantai tidak jelas. Maka, penulis tertarik untuk membahas mekanisme pasar garam rakyat di Indonesia dan dalam persfektif ekonomi konvensional dan Islam. Untuk mengetahui jawaban atas masalah tersebut penulis menggunakan pendekatan kualitatif, untuk menganalisis fenomena yang terjadi terkait dengan analisis teori dan data yang diperoleh. Hasil penelitian menunjukkan bahwa distorsi pasar garam telah terjadi karena adanya praktik monopoli dan ruqban tallaqi. Permasalahan yang terjadi pada sistem perdagangan garam, disebabkan oleh faktor cuaca (curah hujan tinggi), luas lahan yang tidak memadai, teknologi yang masih menggunakan sistem tradisional, standar kualitas garam domestik, kesulitan dalam mencari pasar, indikasi praktik monopoli impor garam.